Efektivitas Terapi Relaksasi Otot Progresif (PMR) Dan Terapi Spiritual Dzikir Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Sinus Agustina, Wahyu; Ikhlasul Amal, Ahmad; Melastuti, Erna; Dwi Retno Sulistyaningsih (An-Najat, 2025)
This study was conducted to evaluate the effectiveness of Progressive Muscle Relaxation (PMR) therapy and spiritual dhikr therapy in reducing blood pressure in hypertensive patients, a condition known to cause various serious health issues. The study design adopted a quasi-experimental approach with a pretest-posttest method and a control group. A total of 36 participants were selected using purposive sampling techniques and divided into two groups: one group receiving PMR and dhikr therapy as treatment, and a control group receiving standard care. Blood pressure measurements were taken before and after the intervention. The study findings revealed a significant reduction in systolic and diastolic blood pressure in the intervention group compared to the control group (p<0.05). These results indicate that PMR and dhikr are effective non-pharmacological approaches for reducing blood pressure in hypertensive patients.